The effect of organizational transformation, organizational culture, and transformational leadership on employee performance through job satisfaction: an evidence from automotive component manufacturing companies - Azmy, Ahmad; Mirza, Mariza; Hartono, Denny Krisnawan (Zielona Góra: Faculty of Economics and Management Press)
This study aimed to analyze organizational transformation, organizational culture, and transformational leadership in relation to employee performance, with job satisfaction serving as a mediating variable. The participants consisted of 101 employees from automotive component manufacturing companies. They were selected using purposive sampling techniques to ensure alignment with the research objectives.
Keywords: organizational transformation; organizational culture; transformational leadership; employee performance; job satisfaction